The Paradigm of Peircean Biosemiotics - Brier, Søren (Signs - International Journal of Semiotics, 2008)
The failure of modern science to create a common scientific framework for nature and consciousness makes it necessary to look for broader foundations in a new philosophy. Although controversial for modern science, the Peircean semiotic, evolutionary, pragmatic and triadic philosophy has been the only modern conceptual framework that can support that transdisciplinary change in our view of knowing that bridges the two cultures and transgresses Cartesian dualism. It therefore seems ideal to build on it for modern biosemiotics and can, in combination with Luhmann’s theory of communication, encompass modern information theory, complexity science and thermodynamics. It allows focus on the connection between the concept of codes and signs in living systems, and makes it possible to re-conceptualize both internal and external processes of the human body, mind and communication in models that fit into one framework.